Acoustic and thermal performance of sustainable fiber reinforced thermoplastic composite panels for insulation in buildings. (August 2021) - Aly, Nermin M.; Seddeq, H.S.; Elnagar, Kh.; Hamouda, Tamer
Abstract: Acoustic and thermal insulation are major issues to be considered in buildings' construction to meet the overall comfort conditions indoors and fulfill the energy-efficiency approaches. This work aimed to investigate the acoustic and thermal insulation performance of sustainable thermoplastic sandwich composite panels to be used in floor systems in buildings. Three types of recycled nonwoven fabrics were used in composites reinforcement; jute, polyester and hybrid jute-polyester (80:20%) with polypropylene as the matrix. Compression molding technique was used in manufacturing of the composite panels with different reinforcement and matrix ratios. The acoustic insulation performance of sandwich composite panels was evaluated in terms of impact sound attenuation test. As well the thermal conductivity was determined and the thermal insulation behavior was investigated using infrared thermography. The results indicated that all composite samples showed increased impact sound reduction at low frequencies. Jute and hybrid jute-polyester composites recorded a decrease in impact sounds reduction at high frequencies, whereas polyester composites showed fluctuated behavior. Increasing the reinforcement and matrix ratios enhanced impact sound reduction for jute composites at high frequencies, and for hybrid jute-polyester composites in the mid and high frequencies. The impact sound reduction index ΔLw values of all composites ranged between 12 and 21 dB. Furthermore, samples PJ and PT produced with 1-layer of reinforcement showed the lowest thermal conductivity and higher resistivity values compared to all samples. The polyester composites were the least samples to gain heat temperature after 60 min, and they exhibited the highest temperature difference compared to jute and hybrid jute-polyester composites. Highlights: Sustainable fiber reinforced thermoplastic composite panels for building insulation. High acoustic insulation of transmitted impact sounds. High thermal insulation of composite panels made of Jute waste and industrial fibers waste. Significant effect of the reinforcement and matrix ratios on acoustic and thermal insulation performance. Thermo-graphical analysis of fabricated composite panels shows material's heat distribution.